AB0879 Pharmacokinetics, Safety, and Tolerability of Tofacitinib in Paediatric Patients from Two To Less than Eighteen Years of Age with Juvenile Idiopathic Arthritis. (15th July 2016) - Ruperto, N.; Brunner, H.I.; Hazra, A.; Wang, R.; Mebus, C.; Alvey, C.; Lamba, M.; Krishnaswami, S.; Conte, U.; Wang, M.; Tzaribachev, N.; Foeldvari, I.; et al.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: Report the pharmacokinetics (PK), safety and taste acceptability of tofacitinib following multiple oral doses in patients (pts) 2-<18 years (yrs) old with active juvenile idiopathic arthritis (JIA). Methods: Data were obtained from an open-label, non-randomised, multicentre, Phase I study (NCT01513902 ) where JIA pts were given 5 mg adult equivalent (based on body weight) of tofacitinib (tablet or solution) twice daily (BID) for 5 days (Table ). There were 3 cohorts (COH) based on pt age, COH1: 12-<18 yrs, COH2: 6-<12 yrs, and COH3: 2-<6 yrs, with a target enrolment per group of ≥8 JIA pts for N=≥24 evaluable pts completing the study. Pts were enrolled in a step-wise approach beginning with the older age COH first. Subsequent younger age COH were enrolled following confirmation of safety and PK from the previous COH. PK parameters of tofacitinib were calculated using non-compartmental analysis of plasma concentration (conc)-time data. Taste acceptability of the solution formulation was listed and categorically summarised (frequency and %). Results: 26 pts (COH1 [N=8], COH2 [N=9] and COH3 [N=9]) were included in this analysis. Pts' age ranged from 2–17 years; all were white race except for one; there were 17 females and 9 males. Baseline disease characteristics were similar across all COH. All exposure metrics including geometric mean (GM) area under the conc-time curves (AUCtau ), maximum (Cmax ), minimum (Cmin ) and predose (Ctrough ) conc were lower in COH2 relative to those in COH1; however, due to higher doses in COH3 (modified after interim analysis of COH1 and 2), the mean AUCtau in COH3 was comparable to COH1. GM apparent volume of distribution (Vz /F) decreased with age (COH1=104.9L, COH2=71.0L, COH3=51.4L). Average terminal half-life (t1/2 ) were COH1=2.62h, COH2=1.95h and COH3=1.77h. GM tofacitinib CL/F were 53%, 39% and 11% higher in COH1, COH2 and COH3 pts, respectively, vs adult RA pts (18.4L/h) receiving tofacitinib 5 mg BID. GM CL/F and V/F parameters were similar between males and females. Tofacitinib, administered over 5 days as multiple dose tablets or solution formulation, was well tolerated and taste for the solution formulation was found acceptable in children with active JIA. No serious adverse events or new safety signals were identified. Conclusions: PK results from this study established dosing regimens for pts aged ≥2 years to be used in the upcoming efficacy and safety studies of tofacitinib in JIA pts. Tofacitinib was well tolerated in this study in JIA pts. Overall, pts found the taste of the tofacitinib solution formulation to be acceptable. Acknowledgement: Study sponsored by Pfizer Inc. Editorial support provided by CMC (funded by Pfizer Inc). Disclosure of Interest: N. Ruperto Consultant for: Abbott, AbbVie, Amgen, Astellas Pharma, Alter, AstraZeneca, Biogen Idec, Boehringer Ingelheim, Bristol-Myers Squibb, CD-Pharma, Celgene, Crescendo Bioscience, EMD Serono, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer Inc, Roche, Sanofi Aventis, Servier, Takeda, Vertex, Speakers bureau: Abbott, AbbVie, Amgen, Astellas Pharma, Alter, AstraZeneca, Biogen Idec, Boehringer Ingelheim, Bristol-Myers Squibb, CD-Pharma, Celgene, Crescendo Bioscience, EMD Serono, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer Inc, Roche, Sanofi Aventis, Servier, Takeda, Vertex, H. Brunner Consultant for: Novartis, Roche, Pfizer Inc, UCB, Celgene, Regeneron, Amgen, AstraZeneca, GlaxoSmithKline, Speakers bureau: Novartis, Roche, A. Hazra Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Mebus Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Alvey Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Lamba Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, U. Conte Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, N. Tzaribachev Grant/research support from: Pfizer Inc, UCB, Roche, I. Foeldvari: None declared, G. Horneff Grant/research support from: AbbVie, Chuigai, Pfizer Inc, Roche, D. Kingsbury Grant/research support from: Pfizer Inc, E. Koskova: None declared, E. Smolewska: None declared, R. Vehe Grant/research support from: Bristol-Myers Squibb, Z. Zuber: None declared, A. Martini Consultant for: Abbott, AbbVie, Amgen, Biogen Idec, Bristol-Myers Squibb, Astellas Pharma, Boehringer Ingelheim, Speakers bureau: Abbott, AbbVie, Amgen, Biogen Idec, Bristol-Myers Squibb, Astellas Pharma, Boehringer Ingelheim, D. Lovell Consultant for: AstraZeneca, Bristol-Myers Squibb, AbbVie, Pfizer Inc, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson & Johnson, Biogen Idec, Takeda, Genentech, GlaxoSmithKline, Boehringer Ingelheim, Celgene, Janssen, Speakers bureau: Genentech, Roche, Novartis